Hidden Gems in the Transcriptome Maps of Competent Streptococci - Junges, Roger; Salvadori, Gabriela; Chen, Tsute; Morrison, Donald A.; Petersen, Fernanda C. (Frontiers in Molecular Biosciences, 2019)
Natural transformation is regarded as an important mechanism in bacteria that allows for adaptation to different environmental stressors by ensuring genome plasticity. Since the discovery of this phenomenon in Streptococcus pneumoniae, remarkable progress has been made in the understanding of the molecular mechanisms and pathways coordinating this process. Recently, the advent of high-throughput sequencing allows the posing of questions that address the system at a larger scale but also allow for the creation of high-resolution maps of transcription. Thus, while much is already known about genetic competence in streptococci, recent studies continue to reveal intricate novel regulation pathways and components. In this perspective article, we highlight the use of transcriptional profiling and mapping as a valuable resource in the identification and characterization of ‘hidden gems’ pertinent to the natural transformation system. Such strategies have recently been employed in a variety of different species. In S. mutans, for example, genome editing combined with the power of promoter mapping and RNA-Seq allowed for the identification of a link between the ComCDE and the ComRS systems, a ComR positive feedback loop mediated by SigX, and the XrpA peptide, encoded within sigX, which inhibits competence. In S. pneumoniae, a novel member of the competence regulon termed BriC was found to be directly under control of ComE and to promote biofilm formation and nasopharyngeal colonization but not competence. Together these new technologies enable us to discover new links and to revisit old pathways in the compelling study of natural genetic transformation.